Social Media Use For Corporate Disclosure Among Public Relations Practitioners In Malaysian Companies: Its Effect On Perceived Organizational Performance - Hashim, Jamsari (2020)
Evidences from past research suggest that social media use in organizations has positive effects on perceived organizational performance. The present study aims to empirically test the relationship in Malaysian context. In doing so, this present study introduces corporate disclosure, drawn from Impression Management Theory (IMT), as the mediator in the relationship between technological, organizational, and environmental factors and perceived organizational performance. In addition, the role of technological, organizational, and environmental factors, deduced from Tornazky & Fleisher’s Technological-Organizational-Environmental Framework (TOEF), were tested as antecedents of social media use for corporate disclosure in the present study. Social media use for public relations functions is tested as a moderator in the relationship between corporate disclosure and perceived organizational performance. Using two theoretical lenses and a body of past research, the study develops a model framework depicting relationships among these variables. This study employed a cross-sectional research to collect data from 120 public relations practitioners in various types of companies in Malaysia. The model was tested using PLS-SEM. Out of eight hypotheses were tested in this study, six were supported.